(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Peptic ulcer embraces both gastric and duodenal ulcers and has been a major threat to the world’s population over the past two centuries, with a high morbidity and substantial mortality. Discovery of gastric mucosa infection with Helicobacter pylori (H. pylori) and its association with chronic antral gastritis and peptic ulcer revolutionized the treatment of ulcer illness. H. pylori are causally related to a majority of cases of both duodenal and gastric ulcer, in the west and developing countries. Despite extensive scientific advancements, this disease remains an important clinical setback, largely because of H. pylori infection and widespread use of non-steroidal anti-inflammatory drugs (NSAIDs). Management of peptic ulcer disease generally involves the practice of H2 receptor antagonists, use of proton pump inhibitors, antacids and different H. pylori eradication regimens. This review article outlines the epidemiology, clinical manifestations, diagnosis and treatment strategies of peptic ulcer disease.